Regulated Deficit Irrigation Alters Anthocyanins, Tannins and Sensory Properties of Cabernet Sauvignon Grapes and Wines - Casassa, Luis Federico (2015)
Four regulated deficit irrigation (RDI) regimes were applied to Cabernet Sauvignon grapes, which were analyzed for phenolics and also made into wine over three consecutive growing seasons. Relative to an industry standard regime (IS), yield was reduced over the three years by 37% in a full-deficit (FD) regime and by 18% in an early deficit (ED) regime, whereas no yield reduction occurred with a late deficit (LD) regime. Relative to IS, skin anthocyanin concentration (fresh weight basis) was 18% and 24% higher in ED and FD, respectively, whereas no effect was seen in LD. Seed tannin concentration was 3% and 8% higher in ED and FD, respectively, relative to the other two RDI regimes, whereas seed tannin content (amount per berry) was higher in IS than in FD. There were no practically relevant effects on the basic chemistry of the wines. The finished wines showed concentrations of tannins and anthocyanins that generally mirrored observed differences in skin and seed phenolic concentrations, although these were amplified in FD wines. Descriptive sensory analysis of the 2008 wines showed that FD wines were the most saturated in color, with higher purple hue, roughness, dryness and harshness, followed by ED wines, whereas IS and LD wines were less saturated in color and with higher brown and red hues. Overall, FD and ED seemed to yield fruit and wine with greater concentrations of phenolics than IS and LD, with the additional advantage of reducing water usage. However, these apparent benefits need to be balanced out with reductions in crop yields and potential long-term effects associated with pre-véraison water deficits